Pelatihan Adaptasi Teknologi melalui Penyusunan E-Modul dengan Menggunakan Flip Pdf Corporate Edition - Fikri, Asyrul; Isjoni, Isjoni; Riantama, M. Yogi; Hasibuan, Rizki Ananda (Universitas Indraprasta PGRI, 2023)
E-modules represent a prominent trend in the ongoing evolution of educational technology. The swift progress of technology necessitates continual adaptation by teachers. This challenge is particularly significant for history teachers who are part of the Indragiri Hulu Regency History MGMP, as they grapple with staying abreast of diverse technological advancements. Consequently, assistance is imperative for these history teachers within the MGMP, specifically in understanding and applying the technology involved in e-module preparation. One effective approach to address this need is to provide support for teachers in utilizing the flip pdf corporate edition for e-module creation. Mentoring is structured across three key stages: preparation, implementation, and evaluation. The initial phase involves developing modules to facilitate independent learning for teachers during the mentoring process. Notably, teachers exhibit high motivation and proficiency in utilizing the application throughout the e-module preparation. They are also capable of crafting autonomous e-modules with the aid of instructional guides. The culmination of this assistance is evident in teachers successfully generating e-modules that can serve as valuable resources for student learning in various subjects. Evaluation results from mentoring activities underscore the importance of teachers consistently and continuously actualizing their knowledge. This ongoing effort is crucial for enhancing literacy and digital skills within the learning process.